Analisis Faktor yang Berhubungan dengan Gangguan Kognitif pada Lansia - Nury Lutfiyatil Fitri; Ludiana Ludiana; Senja Atika Sari; Tri Kesuma Dewi (Universitas Malahayati Lampung, 2025)
ABSTRACT Entering old age, a person will experience various changes and one of them is a change in psychological problems in the form of cognitive disorders. Around 39% of the elderly will experience various symptoms of cognitive impairment such as forgetfulness and increasing age, namely when they are 80 years old, around 85% of the elderly can experience this problem. Factors that can affect cognitive impairment problems in the elderly themselves are not only influenced by age, but can also be influenced by various other factors. The purpose of this study was to determine the factors associated with cognitive impairment in the elderly. This research was conducted using an analytic study, a cross-sectional design, involving 80 elderly people in the Work Area of the Yosomulyo Health Center in 2023. Data analysis was carried out using univariate, bivariate and multivariate analysis. The results showed that the majority of elderly people were aged 65 years (65.0%), female sex (51.3%), primary education (55.0%), health status suffering from medical diseases (52.5%) , and it was found that 27.5% experienced cognitive impairment. Factors that have a significant relationship with cognitive impairment in the elderly are age (OR: 5.885; 95% CI: 1.685-20.548), level of education (OR: 4.617; 95% CI: 1.162-18.354), health status (OR: 4.581; 95% CI: 1.150-18.245) and gender (OR: 3.860, CI95; 1.043-14.283) are the controlling variables. The most dominant variable influencing the occurrence of cognitive impairment in the elderly is the age factor. Keywords: Factors, cognitive impairment, elderly ABSTRAK Memasuki usia lanjut, seseorang dapat mengalami perubahan pada masalah psikis berupa gangguan kognitif. Sekitar 39% lanjut usia akan mengalami berbagai gejala gangguan kognitif seperti mudah lupa dan semakin meningkatnya usia yaitu saat berada pada usia 80 tahun maka sekitar 85% lansia dapat mengalami masalah ini. Faktor yang dapat memengaruhi masalah gangguan kognifi pada lansia sendiri bukan hanya dapat dipengaruhi oleh faktor usia, namun dapat juga dipengaruhi oleh berbagai faktor lainnya. Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang berhubungan dengan gangguan kognitif pada lansia. Penelitian ini dilakukan menggunakan studi analitik, rancangan crossectional, melibatkan 80 lansia di Wilayah Kerja Puskesmas Yosomulyo tahun 2023. Analisa data dilakukan menggunakan analisis univariat, bivariat dan multivariate. Hasil penelitian didapatkan data mayoritas lanjut usia berada pada usia 65 tahun (65,0%), jenis kelamin perempuan (51,3%), pendidikan dasar (55,0%), status kesehatan menderita penyakit medis (52,5%), dan ditemukan sebesar 27,5% yang mengalami gangguan kognitif. Faktor yang memiliki hubungan signifikan dengan gangguan kognitif pada lansia adalah usia (OR: 5,885; CI95%: 1,685-20,548), tingkat pendidikan (OR: 4,617; CI95%: 1,162-18,354), status kesehatan (OR: 4,581; CI95%: 1,150-18,245) dan gender (OR: 3,860, CI95; 1,043-14,283) adalah sebagai variabel pengontrol. Variabel yang paling dominan memengaruhi terjadinya gangguan kognitif pada lansia adalah faktor usia. Kata Kunci: Faktor, Gangguan Kognitif, Lansia